2017
DOI: 10.5713/ajas.16.0836
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of yak (Bos grunniens) gut microbiota during growth revealed by polymerase chain reaction-denaturing gradient gel electrophoresis and metagenomics

Abstract: ObjectiveTo understand the dynamic structure, function, and influence on nutrient metabolism in hosts, it was crucial to assess the genetic potential of gut microbial community in yaks of different ages.MethodsThe denaturing gradient gel electrophoresis (DGGE) profiles and Illumina-based metagenomic sequencing on colon contents of 15 semi-domestic yaks were investigated. Unweighted pairwise grouping method with mathematical averages (UPGMA) clustering and principal component analysis (PCA) were used to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…A better understanding of the rumen microbiome under extensive feeding conditions is essential due to the complexity of the rumen ecosystem, as the manipulation of ruminal microbiota can improve feed efficiency and optimize rumen function [ 52 , 53 ]. Previous studies have demonstrated that changes in rumen microbial communities are affected by several factors, such as ruminant species, age, health, season, geographical location, feed additives, and diet [ 18 , 54 , 55 , 56 ]. Specifically, a diet switch from high forage to high concentrate will definitely cause an enormous change in the rumen bacterial community, which can negatively affect productivity and has the potential to develop metabolic disorders in ruminants [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…A better understanding of the rumen microbiome under extensive feeding conditions is essential due to the complexity of the rumen ecosystem, as the manipulation of ruminal microbiota can improve feed efficiency and optimize rumen function [ 52 , 53 ]. Previous studies have demonstrated that changes in rumen microbial communities are affected by several factors, such as ruminant species, age, health, season, geographical location, feed additives, and diet [ 18 , 54 , 55 , 56 ]. Specifically, a diet switch from high forage to high concentrate will definitely cause an enormous change in the rumen bacterial community, which can negatively affect productivity and has the potential to develop metabolic disorders in ruminants [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on microbial communities and ruminal characteristics are important for understanding and manipulating the health and performance of ruminant animals. Previous studies have shown that changes in rumen microbial communities are affected by factors such as ruminant species, diet, age, health, feed additives, season, and geographical location [2,6,18,19]. In particular, a diet switch from high forage to high concentrate can cause a large change in the rumen bacterial community, which can affect productivity and the potential for metabolic disease in ruminants [20].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, bacteria from the Victivillaceae family and Victivillales order, belonging to the Lentisphaeria class, were more abundant in the SUP+ piglets. The study results demonstrated that this class of bacteria may be involved in the nutrient metabolism of the host, especially in the metabolism of carbohydrates, peptides, and amino acids, and affecting protein utilization and providing beneficial metabolites [ 43 ]; thus, their presence is considered beneficial for the host [ 43 ].…”
Section: Discussionmentioning
confidence: 99%